Incidence rates for complete cusp fracture - Bader, JD, Martin JA, Shugars DA (Blackwell Synergy, 2001)
Although complete cusp fracture is acknowledged to occur frequently, incidence rates have been reported rarely. This study determined incidence rates for complete coronal cusp fracture per person and per tooth type.